Entre a medicalização da infância e a esterilização dos “indesejados”: medicina e eugenia na Parahyba do Norte (1927) - Freire, Leonardo Barbosa Querino (Temporalidades, 2016)
Este trabalho problematiza os diálogos de médicos da cidade de Parahyba do Norte com a eugenia. Este saber teve seu “auge” entre as duas Guerras Mundiais, quando chegou a legitimar a segregação de indivíduos considerados “não aptos” com o objetivo/desculpa de aperfeiçoar as populações humanas. Neste texto, discutimos como as propostas eugênicas foram colocadas em circulação na Parahyba do Norte pelos esculápios que participaram da “Semana Médica”, congresso organizado em maio de 1927 pela Sociedade de Medicina e Cirurgia da Parahyba. As ideias eugênicas desenvolvidas no evento seguiram dois caminhos principais: propostas de medicalização da educação infantil, e defesas do controle sobre a reprodução de indivíduos considerados “indesejados” pelo pensamento eugênico. Para tanto, analisamos os trabalhos apresentados no evento, que foram reunidos em um livro e publicados na imprensa periódica local, a partir da leitura teórica da Nova História Cultural. ABSTRACT: This paper discusses the dialogue between medicine and eugenics in the city of North Parahyba. The eugenics had its “heyday” in the period between the two World Wars, when it legitimized segregation of individuals considered “unsuitable” with the objective / excuse of perfecting human populations. In this article, we discussed how the eugenic proposals were put into circulation in North Parahyba by doctors who participated in the scientific conference "Week of Medicine", organized in the month of May 1927 by the Society of Medicine and Surgery Parahyba. Eugenic ideas developed at the event followed two main paths: medicalization proposals for early childhood education, and the defense of actions to control on the reproduction of individuals considered "undesirable" by eugenic thinking. To this end, we analyze the papers presented at the event, which were brought together in a book, and were also published by the periodical press, from the theoretical reading of the New Cultural History. KEYWORDS: Eugenics, social representations, history of medicine.